2020
DOI: 10.1007/s40333-020-0018-5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of wind erosion and seasonal changes on soil carbon dioxide emission in southwestern Iran

Abstract: Wind erosion is one of the main drivers of soil loss in the world, which affects 20 million hectare land of Iran. Besides the soil loss, wind erosion contributes to carbon dioxide emission from the soil into the atmosphere. The objective of this study is to evaluate monthly and seasonal changes in carbon dioxide emission in four classes i.e., low, moderate, severe and very severe soil erosion and the interactions between air temperature and wind erosion in relation to carbon dioxide emission in the Bordekhun r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Microbes need more energy to cope with the disturbance, which could result in more respiration. For example, studies found an increase in soil respiration along the down-slope transect with increasing erosion rate in different ecosystems (Xiao et al, 2017;Kamali et al, 2020). This increase in soil respiration meant that more CO 2 would be released to the atmosphere and climate warming would be aggravated, suggesting the importance of soil erosion control.…”
Section: Discussionmentioning
confidence: 99%
“…Microbes need more energy to cope with the disturbance, which could result in more respiration. For example, studies found an increase in soil respiration along the down-slope transect with increasing erosion rate in different ecosystems (Xiao et al, 2017;Kamali et al, 2020). This increase in soil respiration meant that more CO 2 would be released to the atmosphere and climate warming would be aggravated, suggesting the importance of soil erosion control.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the temperature is one of the most important factors affecting the activity of microorganisms and soil respiration. The study by Kamali et al [44] investigated the impacts of wind erosion and seasonal changes on soil CO 2 emission and found a positive correlation between air temperature and CO 2 emission.…”
Section: Effect Of Subsurface Drip Fertigation Frequency and Irrigati...mentioning
confidence: 99%
“…Wind erosion affects ~20 Mha of land in Iran, and also affects GHG emissions from soil. Based on experiments conducted at the Iran Research Institute of Forests and Ranges, Kamali et al [40] reported that the highest rate of CO 2 emissions in July was 4.90 g CO 2 /m 2 •d in severely eroded lands and the lowest in January of 0.086 g CO 2 /m 2 •d in less eroded lands. Kamali and colleagues hypothesized that increase in erosion intensity aggravated CO 2 emission rates at severe erosion.…”
Section: Wind Erosion and Gaseous Emissionsmentioning
confidence: 99%